2009
DOI: 10.1002/pola.23386
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and properties of fluorinated polyurethanes

Abstract: Novel fluorinated polyurethanes (FPUs) were prepared by living radical polymerization of polyurethanes and hexafluorobutyl acrylate. The structures of the FPUs were characterized by FTIR, 1H NMR, GPC, DSC, and XPS. The fluorinated polyurethane polymerization was investigated and showed monomer conversion, and molecular weight increased with increasing reaction time. In this way, the fluorine content in polyurethane could be easily adjusted by controlling the content of the fluorinated acrylate monomer. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Recently, we demonstrated the synthesis of PU based on tetraphenyl-1,2-ethanediol to synthesize novel fluorinated polyurethanes (FPU) for biomedical applications [20]. The present work showed that novel PU-I copolymer hydrogels could also be synthesized by this method.…”
Section: Preparation Of Pu-imentioning
confidence: 89%
See 3 more Smart Citations
“…Recently, we demonstrated the synthesis of PU based on tetraphenyl-1,2-ethanediol to synthesize novel fluorinated polyurethanes (FPU) for biomedical applications [20]. The present work showed that novel PU-I copolymer hydrogels could also be synthesized by this method.…”
Section: Preparation Of Pu-imentioning
confidence: 89%
“…The mixture was heated to 60-70°C and allowed to react for 3 h. After 3 h, the temperature was reduced to 30°C, and stoichiometric amounts of tetraphenyl-1,2-ethanediol (TPE) (TPE was prepared according to a method described in a previous publication [20]) and 0.1% dibutyltindilaurate (DBTL) (based on the isocyanate content) were added Scheme 1. Synthesis of PU-I.…”
Section: Preparation Of Pumentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with findings of other authors who worked with fluorine containing polymers. [59][60][61] TGA was carried out to find out the thermal processing window of the PUs synthesized. In order to make components out of biomaterials they have to be heated, melted and shaped using polymer processing machines.…”
Section: Discussionmentioning
confidence: 99%